2013
DOI: 10.9755/ejfa.v25i2.7590
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of salt-tolerant rhizobia native to the desert<br>soils of United Arab Emirates

Abstract: The salinity tolerance of naturally occurring rhizobia, isolated from the root nodules of three leguminous plants, namely sesbania (Sesbania sesban), lablab (Lablab purpureus) and pigeonpea (Cajanus cajan), growing at a research farm in Dubai (United Arab Emirates) was studied. Eight isolates identified from colony morphology and gram staining reaction, when cultured on yeast extract-mannitol agar medium (YEMA) supplemented with different concentration of sodium chloride (NaCl), produced colonies even at salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 12 publications
2
22
0
1
Order By: Relevance
“…According to this particular research there was positive correlation between in vitro stress tolerance and %SE of TCP solubilizer rhizobia isolate at P<0.5. This result was similar to Sharma et al (2013) who concluded that invitro stress tolerance is an indication for the survival and persistence of rhizobial isolates under severe and harsh desert conditions of real in vivo condition. Keyser et al (1979) also reported the positive correlation between Al toxicity tolerances and symbiotic effectiveness of some strains.…”
Section: Resultssupporting
confidence: 90%
“…According to this particular research there was positive correlation between in vitro stress tolerance and %SE of TCP solubilizer rhizobia isolate at P<0.5. This result was similar to Sharma et al (2013) who concluded that invitro stress tolerance is an indication for the survival and persistence of rhizobial isolates under severe and harsh desert conditions of real in vivo condition. Keyser et al (1979) also reported the positive correlation between Al toxicity tolerances and symbiotic effectiveness of some strains.…”
Section: Resultssupporting
confidence: 90%
“…S elec tion of the highes t s alt tol erat e is olate and inoc ulated with specific l egumes enhance t he nodulation and nitrogen fi xation effici enc y of l eguminous plants c ultiv at ed under extrem e envir onm ents (Sharma et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, uma série de fatores afetam a relação simbiótica rizóbio-leguminosa. Estes incluem a compatibilidade com a planta hospedeira e as condições físico-químicas do solo, especialmente salinidade e pH do solo, deficiência de nutrientes, toxicidade de minerais e metais pesados, temperaturas extremas, umidade do solo insuficiente ou excessiva e fatores bióticos tais como a as interações com outros microrganismos do solo (PEREIRA et al, 1999;SHARMA et al, 2013;IYER ;RAJKUMAR, 2017).…”
Section: Rizóbiosunclassified